Effect of CA storage on active oxygen metabolism in Chinese bayberry fruit (Myrica rubra) - XI Yu-fang; LUO Zi-sheng; CHENG Du; XU Cheng; WANG Yi-guang (浙江大学学报. 农业与生命科学版, 2001)
Chinese Bayberry Fruit storaged in 85% N2 delayed the activities declination of Superoxide dismutase (SOD)、Ascorbate peroxidase (APX) and Glutathione reductase (GR) and maintained them at high level. Not only Malondialdehyde (MDA) was hold in a low level, but also the producing rate of active oxygen product rate was inhibited.